PURIFICATION AND FRACTIONAL ANALYSIS OF METHANOLIC EXTRACT OF WEDELIA TRILOBATA POSSESSING APOPTOTIC AND ANTI-LEUKEMIC ACTIVITY - Venkatesh, Uday; Javarasetty, Chethan; Murar, Satish Kumar (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Wedelia trilobata (L.) Hitch (WT), commonly known as yellow dots or creeping daisy, is a shrubpossessing potent biological activities, and is traditionally used a medicinal plant in Ayurveda, Siddha and Unanisystems of medicines, and it has also been tried against leukemia cell line MEG- 01. In the present study, purificationand screening of the plant was done for bioactive compounds in methanolic extract of WT for apoptotic and antileukemiaactivity.Materials and methods: The methanolic extract of WT was initially purified through thin layer chromatography(TLC) and screened for the apoptotic and anti-leukemia activities. The positive band of TLC was subjected to silica gelcolumn chromatography for further purification and the fractions obtained from it were screened again for antileukemiaactivity through thymidine uptake assay and apoptotic activity by DNA fragmentation, nuclear staining andflow cytometry assays. The fraction with positive result was subjected to HPLC for analysis of bioactive components.Results: Out of many combinations of solvents, the methanol and dichloromethane combination in the ratio 6:4 hasrevealed two bands in TLC, among which the second band showed positive results for apoptotic and anti-leukemicactivities. Further purification of second band through silica gel chromatography gave five fractions in which the 3rdfraction gave positive results and it shows single peak during compositional analysis through HPLC.Conclusion: The single peak revealed through HPLC indicates the presence of pure compound with apoptotic and antileukemiaactivities encouraging for further structural analysis.